Electronic Medical Record Prompts for Lab Orders in Patients Initiating Statins - Carroll, D.G.; Alexander, C.; Radford, E.A.; Leeper, J.; Carroll, D.N. (Applied Clinical Informatics, 2011)
Background: The Institute of Medicine (IOM) reports that at least a fourth of all medication related injuries are preventable. Therefore, the IOM recommends healthcare organizations and providers implement electronic prescribing and clinical decision support systems in practices to aid in medication error prevention.Objective: To assess the impact of noninstrusive-intrusive prompts from an electronic medical record on recommended baseline and follow up laboratory monitoring, CK and liver transaminase levels (AST and ALT), in patients initiated on statin therapy.Methods: Hybrid nonintrusive-intrusive prompts for laboratory monitoring specific for statin initiation were implemented in the electronic medical record system in a community based, university affiliated family medicine residency program. A retrospective chart review was conducted to compare and assess laboratory monitoring in patients initiated on statin therapy from two specific time periods: a six month period prior to initiation of the prompts and a six month period after initiation of the prompts.Results: One hundred seventy three patients met inclusion criteria. There were no significant differences in assessment of baseline liver transaminases and CK levels from the initial study period to the follow up study period. There were significant differences in follow up liver transaminase levels (18% vs 33%, p = 0.035) and CK levels (none vs 7%, p = 0.03) from the initial study period to the activated prompt interval.Conclusion: A hybrid nonintrusive-intrusive specific prompts for laboratory monitoring triggered by statin initiation within an electronic medical record improved follow up lab assessments for liver transaminases and CK but did not improve baseline assessments of CK or liver transaminases.
Keywords: Computerized medical records; ambulatory care facilities; clinical laboratory techniques; statins; HMGCOA